133k views
4 votes
What expression gives the distance between the points (4,6) and (7,-3)?

2 Answers

6 votes

By the distance formula,


d = \sqrt{( x_2 - x_1) {}^(2) + (y_2 - y_1 {)}^(2) }

Here,


x_1 = 4


y_1 = 6


x_2 = 7


y_2 = - 3

Hence,


d = \sqrt{( {7 - 4)}^(2) + {( - 3 - 6)}^(2) }


d = \sqrt{ {3}^(2) + ( - {9)}^(2) }


d = √(9 + 81)


d = √(90)

User Amol Patil
by
4.7k points
4 votes

Answer:


√((-3^2-6)+(7^2-4^2))

Explanation:

Use the form:
\sqrt{(x^2-x^1)+(y2-y1)^2

so:
√((-3^2-6)+(7^2-4^2))

User John Driscoll
by
5.2k points